An Assessment of the Effectiveness of Water Quality Monitoring and Drinking Water Quality Compliance by Environmental Health Practitioners at Selected Metropolitan and District Municipalities in South Africa during 2013-2014 - Cele, Aneliswa (Graduate School of Development Policy and Practice, 2019)
Access to safe drinking water is a basic right accorded to all people, and their well-being is critically dependent on both the quality of water and its availability, and how well these are managed. Water quality monitoring is an important activity for ensuring water supplied to the community is safe for human consumption. The legislation safeguarding the delivery of safe water has been evolving and implementation varies. Demand by communities for improvement in services places more pressure on the municipalities. The aim of the study is to assess the water quality compliance and explore the effectiveness of water quality monitoring by Environmental Health Practitioners (EHPs) in South Africa. The aim of the study is to assess the effectiveness of water quality monitoring and the water quality compliance rate in municipalities in the country. The specific objectives of the study:  describe the water quality monitoring system by local municipalities in the country;  assess the compliance rate of domestic water quality samples taken by EHPs per municipality;  assess the staffing norm of EHPs per municipality in comparison to the population served; and  establish the relationship between the results of water compliance rate and the number of EHPs per municipality. A retrospective qualitative and quantitative study was conducted of the water quality compliance rate using the District Health Information System (DHIS) data for the period 2010-2014, with the focus on the period 2013-2014. Detailed analysis was conducted on water quality compliance rate per municipality per month, EHPs staffing norm in municipalities per province, and the compliance rate of domestic water samples taken by EHPs per municipality. The compliance rate was compared to the number of EHPs and also to the population served. Pearson's correlation coefficient (r) was used to test for association of the water quality compliance rate and number of EHPs per Municipality. Data was also analysed on health outcomes, specifically the reports of acute diarrhoea outbreaks during the same year in the North West, KwaZuluNatal and Northern Cape provinces. The results reveal that water quality monitoring is not implemented effectively by most municipalities. The national microbiological compliance rate for the selected municipalities in 2013 to 2014 was at 88.8%, which is below the acceptable compliance standard (100%) in iii terms of SANS 241. It was also observed that the staffing status is not compliant with WHO norms: Mopani District Municipality in Limpopo has a shortage of 95%, and in Amajuba and Zululand District Municipalities in KwaZulu-Natal at 88%. Gaps in the routine data of the DHIS could not allow for a more comprehensive analysis of water quality compliance rate monitoring. Whereas the study has shown a weak positive association between the water quality compliance rate and the environmental health practitioner staffing rate in the municipalities, the Pearson's Coefficient Correlation test results were not statistically significant (R2 =0.0186). The regression line shows a slight positive relationship and the correlation coefficient is also positive. While, a variability may be perceived, it is not statistically obvious nor significant and maybe the result of inappropriate data in the DHIS, tools applied or a flawed assumption of a positive relationship between these two variables. The system exists to ensure a safe drinking water supply to communities. Gaps in legislation, formal guidelines and other contributing factors at different levels need to be addressed by various key stakeholders. As part of the water quality monitoring programme implementation by municipalities, there should be a strong emphasis on data management and communication amongst stakeholder including the Department of Health. Similarly, serious gaps in staffing for environmental health services (70%) need to be addressed to meet the WHO staffing norms. The following are recommended to strengthen water quality monitoring at municipal level: 1. There must be a strong policy to strengthen collaboration among key stakeholders on water provision services: water services authorities, environmental health services and the community to ensure effective and efficient service delivery. 2. Review legislation to harmonise functional powers between different ministries, including reviewing the powers of MECs responsible for health to support environmental health services at municipality level, and look at the roles and responsibilities of other relevant stakeholders. 3. EHPs should be more independent from municipal structures to allow for system that will function more efficiently without any hindrance. 4. The shortage of staff guided by the WHO Norm of 1: 10 000 EHPs per population needs to be addressed by municipalities. 5. Data management including reporting and communication should be strengthened at all levels.